Expression of major histocompatibility complex class I antigens as a strategy for the potentiation of immune recognition of tumor cells. - Tanaka, K (1986)
Like many primary tumors, human adenovirus type 12 (Ad12)-transformed mouse cells express greatly reduced levels of the major histocompatibility complex (MHC) class I antigens and are highly tumorigenic in immunocompetent hosts. Expression of a transfected class I gene by these cells can abrogate their tumorigenicity. Both the K and the L class I genes can suppress the malignant phenotype. Previous studies showed that interferon can induce class I gene expression in certain Ad12-transformed cells and can suppress their tumorigenic phenotype. We now demonstrate that preimmunization of mice with a nontumorigenic dose of interferon-treated Ad12-transformed tumor cells can afford protection against a subsequent challenge by a tumorigenic dose of untreated Ad12-transformed tumor cells. Similar immunity can also be induced by using cells transfected with the K gene, and the observed protection appears specific to Ad12-transformed cells. Significant protection can be achieved even if immunization is provided subsequent to the tumor challenge. Since increasing numbers of human tumors have been found to have reduced levels of MHC class I antigens, the prospect of therapy by immunization with the parental tumor cells that have been manipulated to induce class I gene expression offers an attractive experimental model.